Characterization of a Salmonella typhimurium hisU mutant defective in tRNA precursor processing. - Bossi, L (1978)
The DA11 mutant of Salmonella typhimurium, originally isolated as derepressed for the histidine operon, carries a temperature-dependent alteration in a nucleolytic enzyme specifically involved in the maturation of tRNA. As a consequence of this alteration, no detectable synthesis of any mature tRNA species occurs in DA11 upon shift at 43 degrees C, whereas many tRNA precursors, whose sizes range between 80 and 750 nucleotides, do accumulate. Kinetic studies on the synthesis and processing of these maturation intermediates show that these molecules represent different stages in the maturation pathway, most of them being the products of previous nucleolytic events. These RNA molecules are in vivo substrates of methylation and thiolation enzymes and can be cleaved in vitro to 4S RNA by wild-type but not by DA11 cell-free extract. Evidence is presented that DA11 is very probably a ribonuclease P mutant.